2016
DOI: 10.1080/09513590.2016.1232676
|View full text |Cite
|
Sign up to set email alerts
|

Occult form of premature ovarian insufficiency

Abstract: Premature ovarian insufficiency (POI) is a life-changing diagnosis, with profound physical and psychological consequences. Despite the description of different genetic, immune and iatrogenic factors of POI, the etiology of most cases of this disease are unexplained, and optimal management strategies are still unclear. Recent data showed that POI may have a long period of oligomenorrhea before the fully developed form (complete ovarian failure stage), with the occurrence of amenorrhea and climacteric symptoms. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 10 publications
(12 reference statements)
1
9
0
Order By: Relevance
“…5 used AMH and AFC to assess ovarian function and found that 4.4% of 963 young females (≤30 years) with regular menstruation had OPOI, while Shestakova et al. 20 diagnosed OPOI in 23 patients with unexplained oligomenorrhea and/or infertility. Izhar et al.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…5 used AMH and AFC to assess ovarian function and found that 4.4% of 963 young females (≤30 years) with regular menstruation had OPOI, while Shestakova et al. 20 diagnosed OPOI in 23 patients with unexplained oligomenorrhea and/or infertility. Izhar et al.…”
Section: Discussionmentioning
confidence: 99%
“…Young OPOI patients have normal menstruation, and are usually only diagnosed with decreased ovarian function after an infertility examination. Guzel et al 5 used AMH and AFC to assess ovarian function and found that 4.4% of 963 young females ( 30 years) with regular menstruation had OPOI, while Shestakova et al 20 diagnosed OPOI in 23 patients with unexplained oligomenorrhea and/or infertility. Izhar et al 21 also found that the predictive value of AFC was similar to that of AMH for OPOI.…”
Section: Discussionmentioning
confidence: 99%
“…Premature Ovarian Failure (POF), first described in the 1930s, is a clinical syndrome characterized by a loss of ovarian function before the age of 40 [2] with three sequential stages called occult, biochemical and clinical [3]; corresponding to fertility decline, then an increase in Follicle Stimulating Hormone (FSH) release rate (twice), and finally oligo or amenorrhea [4] respectively. The prevalence of POF among women under 40 years of age is about 1%.…”
Section: Introductionmentioning
confidence: 99%
“…European Society of Human Reproduction and Embryology (ESHRE) [5] recommends both of the following two diagnostic criteria for POI: & oligo/amenorrhea for at least four months & an elevated follicle-stimulating hormone (FSH) level > 25 mIU/ml confirmed twice > 4 weeks apart However, there is a transitional phase of POI when menopausal symptoms and oligomenorrhoea are not yet established [2,[6][7][8], as the disease requires several years to establish its full-blown stage [1,2,7]. In fact, the disorder starts with subfertility (Boccult^or Bincipient^ovarian insufficiency) [8], then it progresses to biochemical insufficiency (elevated levels of FSH) also known as Btransitional phase^of POI [6].…”
Section: Introductionmentioning
confidence: 99%